Modelagem de objetos tridimensionais para um ambiente interativo de instruções técnicas virtuais - NASCIMENTO, Messias José Amador do (Universidade Federal do Pará, 2012)
This dissertation discusses creation paradigms of tridimensional objects, to be used into interactive virtual environments, contextualizing the main techniques for computing implementation of the whole process. As a case study, it was used the Virtual Technical Instructions System, developed by Virtual Reality Laboratory at Federal University of Pará, to Eletronorte S/A, as an auxiliary resource of simulation and training in maintenance and operation procedures at Tucuruí Hydroelectric Power Plant.